Features of radiation damage of Ni-Ti alloy under exposure to heavy ions of gaseous elements; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Poltavtseva V. P.; Kislitsin S. B.; Satpayev D. A.; Mylnikova T. S. Tatyana Stepanovna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2015, 2015)
Title screen